Recent advances and future directions in healthy and innovative technology for the future noodle processing - Naphatrapi Luangsakul; Patranid Mutchadej; Ngô Văn Tài (Future Foods, 2026)
The desire for nutritious food, traceability, and diminished environmental effect is transforming the noodle sector. Noodles are becoming regarded as a structured food system rather than just a convenience product, with component interactions influencing sensory perception, digestibility, shelf life, and environmental impact . This review outlines the recent research from 2021 to 2025 across three main focuses: (i) health and nutrition focuses [low glycemic index (GI), resistant starch (RS), probiotics, targeted micronutrients]; (ii) advancements in processing technology; and (iii) digitalization [artificial intelligence (AI), Internet of Things (IoT), in-line sensors]. Health-related strategies such as increasing RS, soluble fiber, and starch-lipid complexes, along with enhancing amino acid quality, demonstrate significant potential. Alternative flour matrices and hydrocolloids/emulsifiers facilitate the enhancement of protein, fiber, and bioactive while preserving or remaining texture, particularly in gluten-free systems, when utilized within the suitable dose-process parameters. Non-thermal and reactive extrusion technologies enhance shelf life and allow for precise adjustments in starch digestibility; 3D printing is viable when optimizing rheological properties. Non-destructive assessment and in-line quantification are supplanting intuition, facilitating the integration of AI/IoT and enabling real-time control. The proposed roadmap integrates recipe design with process parameterization and real-time detection to achieve products that are delicious, healthy, and environmentally sustainable.
Keywords: Nanocomposite Films for Food Packaging; Advanced Sensor and Energy Harvesting Materials; Advanced Chemical Sensor Technologies